Diversidad genómica de Escherichia coli uropatógena en aislados clínicos de seis países de Latinoamérica, 2018-2023 - Francesca Caballero; Anne Martínez-Ventura; Diego Cuicapuza; Alexander Fajardo-Loyola; Rosmery Gutiérrez Ajalcriña; Javier Soto Pastrana; Percy Asmat-Marrufo; E. Vera; Henry Meza-Fernández; Mario Chambi-Quispe; Jimena Edith Pino-Dueñas; Nicomedes Laura-Rivas; et al. (My University, 2025)
BACKGROUND: Motivation for the study. To contribute to the genomic surveillance of UPEC in clinical samples from Latin America, in response to the growing public health problem represented by UTIs and their resistance to antimicrobials. Main findings. Our study revealed a high frequency of high-risk clones, such as ST131 and ST1193. Critical mutations were identified in genes associated with resistance to multiple antibiotics, including fluoroquinolones, beta-lactams, and fosfomycin. Implications. Our results highlight the urgent need to strengthen UPEC surveillance in Latin America. Tracking resistant strains and implementing measures to limit their spread is crucial and has a significant impact on the effectiveness of available treatments. OBJECTIVE.: To genetically characterize clinical isolates of uropathogenic Escherichia coli (UPEC) from hospitals in Peru and contextualize them against 127 additional UPEC genomes reported in six Latin American countries between 2018 and 2023. MATERIALS AND METHODS.: The genomes of 16 Peruvian UPEC isolates were sequenced, assembled and supplemented with 127 genomes available in the NCBI public database. Serotypes, sequence types (STs), antimicrobial resistance (AMR) genes, and resistance-associated mutations were identified. A phylogenetic analysis was also conducted in order to determine evolutionary relations and distribution in phylogroups. RESULTS.: The ST131 clone was the most prevalent (42.7%), followed by ST1193 (13.3%). Phylogroup B2 was widely predominant (83.2%), with serotype O25:H4 standing out. The resistance genes blaTEM-1, blaCTX-M-15, and blaCTX-M-27 were identified with high frequency, as well as mutations in gyrA and parC associated with fluoroquinolone resistance, especially in the ST131 clone. CONCLUSION.: Our findings show high circulation of high-risk UPEC clones, such as ST131 and ST1193, in Latin America, along with a notable burden of genes and mutations linked to multidrug resistance, highlighting the need to strengthen regional genomic surveillance. BACKGROUND: Motivation for the study. To contribute to the genomic surveillance of UPEC in clinical samples from Latin America, in response to the growing public health problem represented by UTIs and their resistance to antimicrobials. Main findings. Our study revealed a high frequency of high-risk clones, such as ST131 and ST1193. Critical mutations were identified in genes associated with resistance to multiple antibiotics, including fluoroquinolones, beta-lactams, and fosfomycin. Implications. Our results highlight the urgent need to strengthen UPEC surveillance in Latin America. Tracking resistant strains and implementing measures to limit their spread is crucial and has a significant impact on the effectiveness of available treatments.
Keywords: Latin Americans; Diversity (politics); Genetic diversity; Escherichia coli; Biology; Genetics; Microbiology; Evolutionary biology; Gene; Political science; Medicine; Environmental health; Sociology; Anthropology; Law; Population; Latin Americans; Diversity (politics); Genetic diversity; Escherichia coli; Biology; Genetics; Microbiology; Evolutionary biology; Gene; Political science; Medicine; Environmental health; Sociology; Anthropology; Anti-Bacterial Agents pharmacology; Anti-Bacterial Agents pharmacology; Anti-Bacterial Agents pharmacology; Anti-Bacterial Agents pharmacology; Escherichia coli Infections microbiology; Escherichia coli Infections microbiology; Escherichia coli Infections microbiology; Escherichia coli Infections microbiology; Escherichia coli Infections epidemiology; Escherichia coli Infections epidemiology; Escherichia coli Infections epidemiology; Escherichia coli Infections epidemiology; Humans; Humans; Humans; Humans; Latin America; Latin America; Latin America; Latin America; Peru; Peru; Peru; Peru; Phylogeny; Phylogeny; Phylogeny; Phylogeny; Urinary Tract Infections microbiology; Urinary Tract Infections microbiology; Urinary Tract Infections microbiology; Urinary Tract Infections microbiology; Urinary Tract Infections epidemiology; Urinary Tract Infections epidemiology; Urinary Tract Infections epidemiology; Urinary Tract Infections epidemiology; Genetic Variation; Genetic Variation; Genetic Variation; Genetic Variation; Genome, Bacterial; Genome, Bacterial; Genome, Bacterial; Genome, Bacterial; Drug Resistance, Multiple, Bacterial genetics; Drug Resistance, Multiple, Bacterial genetics; Drug Resistance, Multiple, Bacterial genetics; Drug Resistance, Multiple, Bacterial genetics; Uropathogenic Escherichia coli drug effects; Uropathogenic Escherichia coli drug effects; Uropathogenic Escherichia coli drug effects; Uropathogenic Escherichia coli drug effects; Uropathogenic Escherichia coli genetics; Uropathogenic Escherichia coli genetics; Uropathogenic Escherichia coli genetics; Uropathogenic Escherichia coli genetics; Uropathogenic Escherichia coli isolation & purification; Uropathogenic Escherichia coli isolation & purification; Uropathogenic Escherichia coli isolation & purification; Uropathogenic Escherichia coli isolation & purification; Life Sciences Biochemistry, Genetics and Molecular Biology Endocrinology Escherichia coli research studies; Life Sciences Biochemistry, Genetics and Molecular Biology Molecular Medicine Antibiotic Resistance in Bacteria; Health Sciences Medicine Epidemiology Urinary Tract Infections Management